Analisis Pengaruh Corporate Social Responsibility Terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Moderasi: Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019 -2023 - Salvania Ayu Pramudita; Erma Setiawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to determine the determinants of corporate social responsibility on company value with profitability as a moderating variable. This study was conducted using quantitative methods and the population in the study were manufacturing companies listed on the Indonesian Stock Exchange for the period 2019-2023. The sampling technique of this study was using purposive sampling where samples were taken with certain considerations. Data analysis in this study used the help of statistical tools, namely SPSS.